1987
DOI: 10.1111/j.1748-1716.1987.tb08202.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of progesterone and its metabolites on the interictal epileptiform discharge in the cat's cerebral cortex

Abstract: The antiepileptic effect of progesterone, 5-alpha-pregnane-3,20-dione, 3-alpha-hydroxy-5-alpha-pregnane-20-one, and 3-alpha-hydroxy-5-beta-pregnane-20-one were tested in an experimental animal model, and compared with the effect of clonazepam. The steroids were dissolved in serum from ovariectomized cats. Ovariectomized adult cats were used and spontaneous epileptic discharges were generated by placing small pieces of penicillin-soaked filter papers on the ipsi and contralateral cerebral cortex. The frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(41 citation statements)
references
References 24 publications
1
38
0
2
Order By: Relevance
“…Administered intravenously in doses of 0.4–0.6 mg/kg, it produces anesthesia of short duration with minimal effects on hemodynamic and respiratory parameters [9]. Pregnanolone has also been reported to have hypnotic activity [10] and basic research on this class of compounds has demonstrated that compounds closely related to pregnanolone possess hypnotic [11], antiepileptic [12] and anxiolytic activity [13]. Brain and plasma levels of allopregnanolone (3α-hydroxy-5α-pregnan-20-one) temporally follow circulating levels of progesterone produced by the corpus luteum [14].…”
Section: Introductionmentioning
confidence: 99%
“…Administered intravenously in doses of 0.4–0.6 mg/kg, it produces anesthesia of short duration with minimal effects on hemodynamic and respiratory parameters [9]. Pregnanolone has also been reported to have hypnotic activity [10] and basic research on this class of compounds has demonstrated that compounds closely related to pregnanolone possess hypnotic [11], antiepileptic [12] and anxiolytic activity [13]. Brain and plasma levels of allopregnanolone (3α-hydroxy-5α-pregnan-20-one) temporally follow circulating levels of progesterone produced by the corpus luteum [14].…”
Section: Introductionmentioning
confidence: 99%
“…Progesterone depresses neuronal firing (I 8), lessens epileptiform discharges, and elevates seizure threshold in most adult animal models with greater effect in female but not in male rats (5,7,19,20).…”
Section: Progesteronementioning
confidence: 99%
“…Progesterone, because of its anticonvulsive (Backstrom, 1976;Landgren et al, 1987) and anaesthetic (Seyle, 1942;Meyerson, 1967;Norberg et al, 1987) properties, is of particular interest in this context. The central nervous system depression brought about by progesterone is thought to be mediated by metabolites, e.g.…”
Section: Introductionmentioning
confidence: 99%